ALK1 Loss Results in Vascular Hyperplasia in Mice and Humans Through PI3K Activation. Issue 5 (May 2018) - Alsina-Sanchís, Elisenda; García-Ibáñez, Yaiza; Figueiredo, Ana M.; Riera-Domingo, Carla; Figueras, Agnès; Matias-Guiu, Xavier; Casanovas, Oriol; Botella, Luisa M.; Pujana, Miquel A.; Riera-Mestre, Antoni; Graupera, Mariona; Viñals, Francesc
Abstract : Objective—: ALK1 (activin-receptor like kinase 1) is an endothelial cell-restricted receptor with high affinity for BMP (bone morphogenetic protein) 9 TGF-β (transforming growth factor-β) family member. Loss-of-function mutations in ALK1 cause a subtype of hereditary hemorrhagic telangiectasia—a rare disease characterized by vasculature malformations. Therapeutic strategies are aimed at reducing potential complications because of vascular malformations, but currently, there is no curative treatment for hereditary hemorrhagic telangiectasia. Approach and Results—: In this work, we report that a reduction in ALK1 gene dosage (heterozygous ALK1 +/ − mice) results in enhanced retinal endothelial cell proliferation and vascular hyperplasia at the sprouting front. We found that BMP9/ALK1 represses VEGF (vascular endothelial growth factor)-mediated PI3K (phosphatidylinositol 3-kinase) by promoting the activity of the PTEN (phosphatase and tensin homolog). Consequently, loss of ALK1 function in endothelial cells results in increased activity of the PI3K pathway. These results were confirmed in cutaneous telangiectasia biopsies of patients with hereditary hemorrhagic telangiectasia 2, in which we also detected an increase in endothelial cell proliferation linked to an increase on the PI3K pathway. In mice, genetic and pharmacological inhibition of PI3K is sufficient to abolish the vascular hyperplasia of ALK1 +/ − retinas and in turn normalize the vasculature. Conclusions—: Overall, our results indicate that the BMP9/ALK1 hub critically mediates vascular quiescence by limiting PI3K signaling and suggest that PI3K inhibitors could be used as novel therapeutic agents to treat hereditary hemorrhagic telangiectasia. Abstract : Supplemental Digital Content is available in the text.